The diagnostic value of clinical examinations when diagnosing carpal tunnel syndrome assisted by nerve conduction studies - Kucukakkas, OKAN; KÜÇÜKAKKAŞ, OKAN; Yurdakul, OZAN VOLKAN; YURDAKUL, OZAN VOLKAN (My University, 2019)
Background: Our study aims to evaluate the reliability of clinical findings in diagnosing carpal tunnel syndrome (CTS), with the help of nerve conduction studies (NCSs) and the detection of comorbidities likely to be risk factors.